2019
DOI: 10.1111/dmcn.14390
|View full text |Cite
|
Sign up to set email alerts
|

Seizure freedom improves health‐related quality of life after epilepsy surgery in children

Abstract: Aim To determine whether epilepsy surgery improved health‐related quality of life (HRQoL) and whether seizure freedom after surgery mediated the improvement in HRQoL. Method This multicenter cohort study compared HRQoL after epilepsy surgery to pharmacological management in children with drug‐resistant epilepsy (DRE). HRQoL was measured using the Quality of Life in Childhood Epilepsy (QOLCE) questionnaire at baseline and 1‐year follow‐up. The mediator between treatment type and HRQoL was seizure freedom. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…This is consistent with our previous research examining child HRQOL, 36 which found that seizure freedom mediated the relationship between treatment and HRQOL at 1-year follow-up; children who had surgery were more likely to achieve seizure freedom, which in turn was associated with improved HRQOL. 36 These findings are also consistent with our prior study that showed seizure freedom, rather than treatment type, was associated with better emotional functioning, one dimension of HRQOL. 37 This multisite study employed a longitudinal design with children followed up for 1 year and utilized data that were prospectively collected.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with our previous research examining child HRQOL, 36 which found that seizure freedom mediated the relationship between treatment and HRQOL at 1-year follow-up; children who had surgery were more likely to achieve seizure freedom, which in turn was associated with improved HRQOL. 36 These findings are also consistent with our prior study that showed seizure freedom, rather than treatment type, was associated with better emotional functioning, one dimension of HRQOL. 37 This multisite study employed a longitudinal design with children followed up for 1 year and utilized data that were prospectively collected.…”
Section: Discussionsupporting
confidence: 91%
“…Steinbok et al in a multicenter study of 116 infants (up to 3 years of age) report a developmental improvement in most children following surgery 25 . Others state stabilization of developmental impairment following surgery, 32 and that postsurgical developmental status positively correlated with preoperative developmental status 15 . Dunkley et al speculated that cognitive injury occurs early in the epileptic course, and is often irreversible 27 .…”
Section: Discussionmentioning
confidence: 99%
“…100 Moreover, the benefit on quality of life, cognitive evolution, particularly for children, and psychiatric comorbidities is positive. [108][109][110] This global benefit is also stated in more specific populations, including children with autism spectrum disorders 111 or older adults (more than 60 years). 112 It should be emphasized that lesion on MRI is not a prerequisite for epilepsy surgery.…”
Section: Epilepsy Surgerymentioning
confidence: 96%